The Influence of Work Environment, Work Discipline, and Work Incentives on The Performance of Employees at The Directorate of Directors of DKI Jakarta - Zahirah, Fildzah Dini; Digdowiseiso, Kumba; Krisnandi, Herry (International Journal of Social Service and Research, 2024)
This study aims to analyze the influence of the Work Environment, Work Discipline, and Work Incentives on the Performance of the DKI Jakarta Bina Marga Service Employees. This study uses primary data and the data collection method used for the results of material analysis is to use a questionnaire or questionnaire from 100 respondents. The method used in this research is quantitative. The results of this study show that the Work Environment, Work Discipline, and Work Incentives simultaneously affect the Performance of the DKI Jakarta Bina Marga Service Employees.